2012
DOI: 10.1039/c2sc20443f
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO2 uptake and inverse CO2/C2H2 selectivity in a dynamic bifunctional metal–organic framework

Abstract: The unique bifunctional porous metal-organic framework, [Co(HL dc )]$1.5MeOH$dioxane, incorporates both free-standing carboxyl and pyridyl groups within its pores. Gas adsorption measurements on the desolvated framework reveal unusual selective CO 2 adsorption over C 2 H 2 and CH 4 linked to a framework phase change from a narrow pore (np) to a large pore (lp) form, mediated by CO 2 uptake at 195 K. This phase transition has been monitored by in situ powder X-ray diffraction and IR spectroscopy, and modelled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
78
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 53 publications
3
78
0
Order By: Relevance
“…Several reported MOFs possess dynamic constituents, e.g., bridging ligands that can rotate, while maintaining an approximately rigid unit cell (18,(24)(25)(26)(27)(28)(28)(29)(30)(31)(32)(33)(34). Nuclear magnetic resonance (NMR) spectroscopy revealed that aromatic rings in the ligands of MOF-5 (26), IRMOF-3 (27), and MIL-47(V) (35) rotate, resembling an ordered assembly of molecular rotors (36).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several reported MOFs possess dynamic constituents, e.g., bridging ligands that can rotate, while maintaining an approximately rigid unit cell (18,(24)(25)(26)(27)(28)(28)(29)(30)(31)(32)(33)(34). Nuclear magnetic resonance (NMR) spectroscopy revealed that aromatic rings in the ligands of MOF-5 (26), IRMOF-3 (27), and MIL-47(V) (35) rotate, resembling an ordered assembly of molecular rotors (36).…”
mentioning
confidence: 99%
“…When the dominant conformations of these flexible parts in MOFs are different in the evacuated solid than in the presence of gas, the dynamic moieties can qualitatively affect the adsorption behavior, e.g., by inducing inflections (30), steps (29), and hysteresis (18) in the adsorption isotherms. Linkers in ZIF-7 are believed to rotate and cause steps and hysteresis in the adsorption isotherms of several hydrocarbons (39,40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11,[14][15][16][17] This behaviour results in stepped adsorption isotherms, which may exhibit a hysteresis that can be exploited in gas capture or separation applications. [18][19][20] The most well-studied MOFs that exhibit such defined transitions are those with a pillared or columnar structure that contain 1D channels with a diamond or square cross-section, which compress or expand upon breathing in a manner analogous to that of a wine-rack. Such MOFs include the paddlewheel MOF DMOF, [21][22][23] [Zn 2 (BDC) 2 (dabco)] (BDC = 1,4-benzenedicarboxylate or derivatives; dabco = 1,4-diazabicyclooctane) and azolate MOFs [M(BDP)] (M = Fe, Co; BDP = 1,4-benzenedipyrazolate).…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] MOFs are compounds containing metal nodes (metal ions or clusters) coordinated to organic linker molecules that form the extended network structures with unique physical and chemical properties. The ability to tailor and control the density, internal pore volume and the internal surface area of MOFs 19,20 is crucial for utilizing these materials in high capacity gas uptake applications.…”
Section: Introductionmentioning
confidence: 99%